Skill qualities as risk factors for contact injury in professional rugby league players - Gabbett, T. J.; Ullah, S.; Jenkins, D.; Abernethy, B. (Journal of Sports Sciences, 2012)
We investigated the relationship between skill qualities and contact injury risk in professional rugby league players. Sixty-six professional rugby league players aged 23 ± 4 years (mean ± s) participated in this three-year prospective study. Players underwent assessments of tackling proficiency, dual-task draw-and-pass proficiency, reactive agility, pattern recall, and pattern prediction. The frailty model was applied to calculate the adjusted risk ratios of injury. When the players' age and playing position were adjusted in the frailty model, the risk ratios showed that reactive agility was a predictor for the risk of injury. Players with reactive agility decision times of >80 ms had a lower incidence (relative risk = 0.68, 95% CI 0.47-0.98, P = 0.04) of injuries than players with reactive agility decision times of =80 ms. Although there was no relationship between injury and the majority of skill qualities (P = 0.47-0.93), players with poor reactive agility performances (specifically longer decision times) had a lower risk of injury, suggesting that poor perceptual skill is protective against contact injuries in professional rugby league players. These players might inadvertently avoid the heavy collisions that result in injury, or at best result in partial contact that does not result in exposure to the full force of a tackle.